Development and Implementation of a National Programme for the Management of Severe and Very Severe Pneumonia in Children in Malawi - Enarson, Penelope Marjorie; Gie, Robert; Enarson, Donald A.; Mwansambo, Charles (PLoS medicine, 2009)
Penelope Enarson and colleagues describe the development, scale-up, and achievements of a national pneumonia program in Malawi, which is based on a successful anti-tuberculosis service delivery model.